Cultures of contamination legacies of pollution in Russia and the U.S. - Edelstein, Michael R.; Tysiachniouk, Maria; Smirnova, Lyudmila V. (Research in social problems and public policy ;, 2007)
This volume ponders the cultures that generated the bulk of our global contamination legacy. Insight is sought into its creation and an understanding of differences in how it is being addressed. Hopefully the illumination of the problem will contribute to a better understanding of the constraining conditions and will help guide us in meeting the twin challenges created by the legacy of contamination: how to stop it and how to address what we already have done. Section one focuses on the psycho-social dynamics of chemical contamination. Section two deals with nuclear events, both accidents, but also the closed cities and closed society needed to produce a nuclear context. Section 3 addresses mitigations, dominated by 4 out of 5 chapters addressing Russia. And section four provides perspectives, comparative pieces addressing secrecy in nuclear programs, distorted risk communication in the aftermath of the World Trade Center Disaster, environmental altruism and in core social response to environmental challenges. It examines the cultures most responsible for global contamination. It adopts a global and practical perspective, with case examples from the United States and Russia. It seeks to stop contaminations from taking place in the future and positively address those from the past. This book series is available electronically at website.